Option of Inspection and its applications in Takhar Province – Afghanistan - Hamedi, Atiqullah; Karimi, Abdul Wahid (Journal of Humanities and Social Sciences Studies, 2023)
The topic of "option of inspection" is one of the topics that old and contemporary jurists talked about and conveyed different opinions on this issue. It means that the purchaser has the right to sign the contract or rescind it upon seeing the thing contracted for if he did not see it at the creation of the contract or before it. Selling has become common among merchants without the buyer seeing the sold item in general, due to the development of types of sale and their holding between the followers of different countries and through modern means of communication, in which the buyer does not see the sale in most of its forms, except after moving from one store to another, and due to not seeing it, he can be able to do so. The type of sales is some deception, so the purchaser of absent objects needs to prove the option of seeing, in order to ward off the illusions of deception. We wanted to do research on this topic to reveal its different angles. The purpose of the current study is to find out the correct opinion about it and explain it to people. In order to find his legal ruling, we searched for him in the expressive books and the opinions of the jurists of the ancients, the later ones, and the contemporary, and to find out the most correct saying in the quality of the proof of the vision option, we conducted a dialogue with scholars, sheikhs, university professors, and merchants in the form of questionnaires that are mentioned in the last pages.